The effect of salivarus on the immune response to Newcastle and Gumboro disease vaccines and on performance - Shalash, Ali A.H.; Al-Oubaidi, Ebtesam G. A. (The Iraqi Journal of Veterinary Medicine, 2003)
A total of 50 day - old broiler chicks were divided equally into two groups and treated with Lactobacillus salivarus (L S) as follow Group 1: given 3.2X108 cfu/ ml of LS in crop at day 1 of age. Group 2:Untreated control The two groups were vaccinated against Newcastle disease vaccine (ND vac) Lasota strain at age 10, 21, and 35 days direct in the crop. The groups were vaccinated in the crop against Gumboro vaccine (G vac) leukert strain at 5, 14 and 24 day of age. Haemagglutination inhibition test was used and determine antibodies titer (Abt) of (ND vac) and the agar gel precipitating test to 19, 29 and 39 of the chick’s age. The result showed significant (p < 0.05) increase in Abt most of the weeks in the first group compared with second groups The performance results showed significant (p < 0.05) increase in the weight, weight gain , feed consumption and feed conversion ratio for chicks treated with LS. It was concluded that oral administration of Lactobacillus salivarus to day – old chicks has a beneficial effect on immune response to ND vac and G vac and on chick’s performance.